The making of American Buddhism - Mitchell, Scott A. (Oxford scholarship online, 2023)
This volume looks at the intersection of race and religion in the United States before, during, and after World War II, when Nisei (second-generation) Japanese American Jodo Shinshu (or Shin) Buddhists reacted to the trauma of racial and religious discrimination.